HYBRIDITY POTRAYED BY MAJOR CHARACTERS IN THE NOVEL “CRAZY RICH ASIAN” BY KEVIN KWAN - Yolanda Viviani; Robby Satria Mandala (Universitas Putera Batam, 2021)
This research was conducted to figure out kinds of hybridity that major characters did in the novel “Crazy Rich Asian” by Kevin Kwan. This study was analyzed by using postcolonial approach with theory of hybridity by Homi K. Bhabha. According to Bhabha, hybridity is the mixing of two or more different culture and create a new culture that has both culture characteristic. It can be said that hybridity is the result of cross culture that appears in society due to cross cultural interaction that happened for a long time. Descriptive qualitative method was used in this research to analyse social problems happened in the novel. Based on the analysis that had been conducted, there were two kinds of hybridity found out in the novel “Crazy Rich Asian”. They are ethic hybridity and lifestyle hybridity. The ethic hybridity was found in Rachel and Eddie’s mindset. Their mindset were more like American than other characters. Lifestyle hybridity was found in Astrid lifestyle which more like westerner than her husband.